Elasticity and cross-sectional thickness of paraspinal muscles in progressive adolescent idiopathic scoliosis - Yunli Fan; Yunli Fan; Haiping Zheng; Lin Feng; Michael K. T. To; Michael K. T. To; Guan-Ming Kuang; Eric H. K. Yeung; Kenneth M. C. Cheung; Kenneth M. C. Cheung; Li Liu; Jason P. Y. Cheung; et al. (Frontiers Media S.A., 2024)
Objectives(1) Compare the cross-sectional thickness (CST) and shear wave speed (SWS) of paraspinal muscles (PSM) in adolescent idiopathic scoliosis (AIS) with and without curve progression; (2) investigate the relationship between CST/SWS and radiographic characteristics in AIS with curve progression; (3) compare the CST/SWS between AIS and non-scoliosis controls.MethodsThis cross-sectional study analyzed the CST and SWS of PSM in 48 AIS with mild to moderate curvature and 24 non-scoliosis participants. Participants with scoliosis greater than 45° of Cobb angles were excluded. The Change of Cobb angles within the last 6-months was retrieved to allocate AIS into progression and non-progression groups. The SWS and CST of multifidus; longissimus and iliocostalis of the major curve were measured using B-mode ultrasound image with an elastography mode. Discrepancies of the SWS (SWS-ratio: SWS on the convex side divided by SWS on the concave side) and CST (CST-ratio: CST on the convex side divided by CST on the concave side) at the upper/lower end and apical vertebrae were studied.ResultsA higher SWS at the apical vertebrae on the concave side of the major curve (multifidus: 3.9 ± 1.0 m/s vs. 3.1 ± 0.6 m/s; p < 0.01, longissimus: 3.3 ± 1.0 m/s vs. 3.0 ± 0.9 m/s; p < 0.01, iliocostalis: 2.8 ± 1.0 m/s vs. 2.5 ± 0.8 m/s; p < 0.01) was observed in AIS with curve progression. A lower SWS-ratio at apical vertebrae was detected with a greater vertebral rotation in participants with curve progression (multifidus [grade II]: 0.7 ± 0.1 vs. grade I: 0.9 ± 0.2; p = 0.03, longissimus [grade II]: 0.8 ± 0.2 vs. grade I: 1.1 ± 0.2; p < 0.01). CST was not different among the progressive, non-progressive AIS and non-scoliosis controls.ConclusionsIncreased SWS of PSM without change of CST was observed on the concave side of the major curve in participants with progressive AIS.